ETNOBOTANI BAMBU OLEH MASYARAKAT DI SEKITAR HUTAN DESA LANDAU GARONG KABUPATEN MELAWI - Retnawati, Wiwin; Wardenaar, Evy; Kartikawati, Siti Masitoh (Universitas Tanjungpura, 2020)
The people of Landau Garong village have a direct relationship with plants in their traditional use (ethnobotany), especially bamboo. Bamboo in the village is very abundant so that many people use it in various needs according to their skills. The purpose of this study was to record and document the types used and find out patterns of utilization of bamboo by the community around the village forest Landau Garong Melawi district. The benefit of this research is to inform the community outside the Landau Garong village about the types of bamboo and their sustainable use patterns by the community around the Landau Garong village forest. This study uses a survey method with data collection techniques using the PRA method. Data obtained through observation and interviews. Data collected in the form of primary data and secondary data. Based on the results in the field, I obtained 6 types of bamboo, namely Gigantochloa hasskarliana, Bambusa vulgaris var.vulgaris, Schizostachyum brachycladum, Schizostachyum flexuosum, Gigantochloa balui dan Gigantochloa levis. There are 6 types of use of bamboo by the community, namely as building materials, craft materials (household crafts and fish trap crafts), food ingredients, traditional ritual materials, agricultural equipment materials, and traditional game materials. Keywords: Ethnobotany, Bamboo, Community Around The Forest, Landau Garong Village